A E I O U - Cervantes, Jesus P.; Bernales, Carlos E. (New York : Scholastic, 1998)
A girl is helped by her mother to learn the vowels a, e, i, o, and u.
In Spanish.
Keywords: Reading -- Phonetic method; Spanish language materials